Pengaruh Promosi Terhadap Keputusan Konsumen Dalam Memilih Maskapai Penerbangan Citilink Rute Pekanbaru-Jakarta - Wicara, Dinda Genta; Yuliaty, Hefny (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The research was conducted at PT. Citi Link Indonesia in Pekanbaru. The aim of this research is to determine the effect of promotions on consumer decisions in choosing an airline for the Pekanbaru - Jakarta route. Data analysis in this research used qualitative and quantitative descriptive methods with a sample of 100 respondents from 48,818 existing populations and analyzed using a simple linear regression method. The results of data processing showed that the average value of the sales promotion variable was in the agree or good category, namely on an interval scale of 4.13. Based on the results of a simple regression test, it can be seen that the value of t_count > t_table (6.509 > 1.985) and significance < 0.05 (0.000 < 0.05), then Ha is accepted, meaning that promotion has a positive and significant effect on the decision to choose Citilink airline for the route. Pekanbaru Jakarta. The R square value obtained is 0.302 or 30.2%, meaning that the promotional variable has an influence on the decision to choose Citilink airline for the Pekanbaru Jakarta route by 30.2% and the remainder (100-30.2%) = 69.8% is influenced by the variable others not examined in this study.